2021
DOI: 10.4103/jpbs.jpbs_553_20
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Mesh versus Medpor Implant in Orbital Floor Reconstructions: A Comparative Study

Abstract: Background: Treating orbital injuries is interesting and difficult in the facial trauma. The balance in facial proportions and also the facial esthetics are required to achieve an anatomical harmony. Objective: To compare the functional results of individual reconstruction of orbital floor using either titanium mesh or Medpor in terms of various factors. Materials and Methods: There were two study groups including eight subjects with orbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Metallic materials, with titanium being the most widely used, remain the preferred gold standard for orbital floor reconstruction nowadays [27][28][29][30]. Titanium's exceptional biocompatibility, corrosion resistance, and mechanical properties closely resembling natural bone make it a preferred choice.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallic materials, with titanium being the most widely used, remain the preferred gold standard for orbital floor reconstruction nowadays [27][28][29][30]. Titanium's exceptional biocompatibility, corrosion resistance, and mechanical properties closely resembling natural bone make it a preferred choice.…”
Section: Metalsmentioning
confidence: 99%
“…Commercially available PE sheets of varying sizes and thicknesses can be easily adapted for individual cases, promoting tissue ingrowth while minimizing complications such as foreign body reactions [63][64][65]. A recent comparative study of Medpor versus titanium mesh by Marella and colleagues found that Medpor significantly lowered pain and enophthalmos scores, while both groups had comparable outcomes for all other parameters [28]. While it lacks radiodensity and might not be easily visualized on post-operative CT scans, Medpor is generally well-received by the body and its porous architecture enables the formation of fibrovascular networks, serving as a safeguard against infections and implant displacement [66].…”
Section: Porous Polyethylene (Pe)mentioning
confidence: 99%
“…The study found that Medpor ® was more effective in reducing pain and enophthalmos than titanium mesh. However, for all other evaluated parameters, both groups showed comparable outcomes [ 33 ]. Despite its general acceptance, complications such as implant extrusion and infection have been reported [ 34 , 35 , 36 ].…”
Section: Oculoplastic and Orbital Surgery Devicesmentioning
confidence: 99%